2018
DOI: 10.1007/s11136-018-1792-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extended half-life versus conventional factor product on hemophilia caregiver burden

Abstract: IntroductionExtended half-life factor products have reduced annualized bleeding rates in hemophilia patients. The impact of extended half-life versus conventional factor products on hemophilia caregiver burden has not been investigated. This study aimed to evaluate caregiver burden in extended half-life versus conventional factor products for hemophilia A and B.MethodsThis cross-sectional web-based study of caregivers of people with hemophilia A or B was recruited from a panel research company and by word of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
3
31
0
1
Order By: Relevance
“…We have shown in our study that bleeding impacts on caregivers' burden, causing emotional stress, changed perception of the child and the need for more medical management. This concurs with a recent study by Schwartz et al, 28 who demonstrated an association between caregiver burden and number of bleeds in the past 6 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have shown in our study that bleeding impacts on caregivers' burden, causing emotional stress, changed perception of the child and the need for more medical management. This concurs with a recent study by Schwartz et al, 28 who demonstrated an association between caregiver burden and number of bleeds in the past 6 months.…”
Section: Discussionsupporting
confidence: 93%
“…We have shown in our study that bleeding impacts on caregivers’ burden, causing emotional stress, changed perception of the child and the need for more medical management. This concurs with a recent study by Schwartz et al, who demonstrated an association between caregiver burden and number of bleeds in the past 6 months. Tackling bleed management, particularly if this requires hospital visits, is known to be difficult for parents, who describe loss of control and additional stress .…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers who spent more time travelling to the HTC and needed more time to infuse their child per month reported greater caregiver burden, and this was in line with data from caregivers in the United States . Schwartz et al described in another US study of haemophilia caregivers worse social, physical, emotional, financial and life style impact as well as overall burden related to number of infusions per week. Little et al describe how living nearer to treatment centres reduced parental stress and improved treatment satisfaction, well‐being and ability to work full‐time.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, the parents may have reduced working hours, high out-of-pocket healthcare expenses and difficulties with childcare. Haemophilia might have likewise psychosocial effects on the parents (von der Lippe, Frich, Harris, & Nyheim Solbraekke, 2017; Saxena, 2013;Schwartz et al, 2018). Previous qualitative studies on parents of children with haemophilia revealed that parents experience feelings of guilt, anxiety, despair, vulnerability and powerlessness (Furmedge, Lima, Monagle, Barnes, & Newall, 2013;Myrin Westesson, Baghaei, & Friberg, 2013;Myrin Westesson, Sparud-Lundin, Wallengren, & Baghaei, 2015;Myrin Westesson et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Haemophilia is a rare but serious chronic bleeding disorder, and when a child is diagnosed with severe or moderate haemophilia, the whole family becomes affected by the illness (Myrin Westesson, Wallengren, Baghaei, & Sparud-Lundin, 2018;Saxena, 2013;Schwartz, Powell, Su, Zhang, & Eldar-Lissai, 2018). Prophylactic treatment with clotting factor is the standard treatment for children with severe haemophilia in high-income countries (Bertamino, Riccardi, Banov, Svahn, & Molinari, 2017).…”
Section: Introductionmentioning
confidence: 99%